Cytotoxic activity of NN-32 toxin from Indian spectacled cobra venom on human breast cancer cell lines - Saurabh S. Attarde; Sangeeta V. Pandit (BMC, 2017)
Abstract Background Breast cancer is the most common cancer which causes significant morbidity and mortality among women worldwide. Lack of medical facilities for early detection, therapeutic strategies for treatment and side effects due to pharmacological compounds have encompassed the need for new therapies mostly from natural sources. A lot of components have been identified from different snake venoms as therapeutic agents. A group of polypeptides (60-70 amino acid residues) called cytotoxins or cardiotoxins present in an elapid family of snakes have a wide variety of pharmaceutical actions and have the tendency to damage a wide variety of cells including cancerous cells. The aim of the present study was to evaluate the cytotoxic effect of NN-32 protein toxin purified from Indian Spectacled Cobra venom against human breast cancer cell lines (MCF-7 and MDA-MB-231). Methods The NN-32 toxin was purified by ion exchange chromatography and further by RP-HPLC. The potential anticancer effects of the NN-32 toxin on MCF-7 and MDA-MB-231 cells were evaluated using MTT, anti-proliferation, neutral red (NR) uptake and Lactate Dehydrogenase (LDH) release assay. Results The ion exchange chromatography showed various peaks among fraction no. 35 showing cytotoxic activity and this fraction showed a single peak with retention time 3.6 mins by HPLC using C18 column. The NN-32 toxin induced cytotoxicity in MCF-7 and MDA-MB-231 cells with the IC50 value of 2.5 and 6.7 μg/ml respectively. The NN-32 showed significant cytotoxicity to both the cell lines along with low cytotoxicity to MCF-10A (normal breast epithelial) cells. The cytotoxic effect was further confirmed by the anti-proliferative, NR uptake and LDH release assays. Conclusion The purified toxin NN-32 from Naja naja venom showed cytotoxic activity against MCF-7 (ER+) and MDA-MB-231(ER-) cells in both dose dependent and time dependent manner.